2014
DOI: 10.1080/14728028.2014.928604
|View full text |Cite
|
Sign up to set email alerts
|

Status, distribution and use of threatened tree species in the walnut-fruit forests of Kyrgyzstan

Abstract: Information is lacking on the status of threatened tree species in Central Asia. This paper aims to provide preliminary information for 10 fruit and nut tree species of Kyrgyzstan. A field survey was conducted throughout the range of walnut-fruit forests in this country, supported by a socio-economic survey. Results indicated that species differed markedly in abundance. Whereas Malus sieversii was found in all locations, four species (Crataegus pontica, Pistacia vera, Pyrus korshinskyi and Sorbus persica) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…The threat analysis and the observations of livestock presence in protected areas during field work support the view that walnut populations located within protected areas are not sufficiently protected. Orozumbekov et al (2014) observed frequent signs of livestock browsing on seedlings and saplings in sample plots in the Sary-Chelek Reserve and confirmed the common assumption that scarce natural regeneration of fruit trees in walnut forests is attributable to overgrazing. Although grazing and logging are illegal in the majority of the state-owned forests in the region, they are common practice (Eastwood et al, 2009).…”
Section: Distribution and Threatssupporting
confidence: 76%
See 4 more Smart Citations
“…The threat analysis and the observations of livestock presence in protected areas during field work support the view that walnut populations located within protected areas are not sufficiently protected. Orozumbekov et al (2014) observed frequent signs of livestock browsing on seedlings and saplings in sample plots in the Sary-Chelek Reserve and confirmed the common assumption that scarce natural regeneration of fruit trees in walnut forests is attributable to overgrazing. Although grazing and logging are illegal in the majority of the state-owned forests in the region, they are common practice (Eastwood et al, 2009).…”
Section: Distribution and Threatssupporting
confidence: 76%
“…The most important threats in the region and in each country are overgrazing and overexploitation. This is a serious and growing problem for walnut, highlighted in previous studies (Beer et al, 2008;Eastwood et al, 2009;Cantarello et al, 2014;Orozumbekov et al, 2014).…”
Section: Distribution and Threatsmentioning
confidence: 94%
See 3 more Smart Citations